Adhesion and bonding of Pt/Ni and Pt/Co overlayers: density functional calculations - Cabeza, Gabriela Fernanda (2006)
The electronic and energetic properties of bimetallic surfaces Pt/Ni(111) and Pt/Co(111) are examined using the FP-LAPW (Full-Potential Linearized Augmented Plane Wave) method by means of spin-polarized and non-polarized calculations. We present both the results of the shifts in the d-band centers when one metal (Pt) is pseudomorfically deposited on another with smaller lattice constant (Ni, Co) and those corresponding to the surface and adhesion energies. The surface is modeled by a seven layer slab separated in z direction by a vacuum region of six substrate layers. The results obtained for pure Ni, Co and Pt surfaces are presented in order to compare with experimental and theoretical data reported in the literature © 2005 Elsevier Ltd. All rights reserved.